1999
DOI: 10.1051/hydro:1999002
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse des dix premières années de suivi hydrobiologique du Rhône au niveau de la centrale nucléaire de Saint-Alban (France)

Abstract: Résumé. -Le bilan des dix premières années de suivi de l'influence du rejet d'eau de refroidissement de la centrale nucléaire de Saint-Alban, implantée sur le Rhône environ 50 km à l'aval de Lyon, a permis d'établir que les caractéristiques physiques, chimiques et biologiques du Rhône-Moyen sont issues, en premier lieu, de l'anthropisation du fleuve et de sa vallée. D'un point de vue biologique, le système a dérivé vers un type potamique lent, composé d'espèces ubiquistes et résistantes et de quelques espèces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Chlorophyll a concentrations mainly reflect the abundance patterns of diatoms and chlorophyll b those of chlorophytes (Hellings et al 1999;Lemaire et al 2002;Lionard et al 2008). In Western European rivers, diatoms usually dominate the phytoplankton community (Lemaire et al 2002;Lionard et al 2008), as also previously observed in the Rhone River (Fruget et al 1999). In the present study, two peaks in Chl a were observed in the Rhone in 2005, the first in March corresponding to the spring bloom, and the second in June and early summer.…”
Section: Phytoplankton Importance and Compositionmentioning
confidence: 81%
See 1 more Smart Citation
“…Chlorophyll a concentrations mainly reflect the abundance patterns of diatoms and chlorophyll b those of chlorophytes (Hellings et al 1999;Lemaire et al 2002;Lionard et al 2008). In Western European rivers, diatoms usually dominate the phytoplankton community (Lemaire et al 2002;Lionard et al 2008), as also previously observed in the Rhone River (Fruget et al 1999). In the present study, two peaks in Chl a were observed in the Rhone in 2005, the first in March corresponding to the spring bloom, and the second in June and early summer.…”
Section: Phytoplankton Importance and Compositionmentioning
confidence: 81%
“…Spring blooms of diatoms are observed regularly in other rivers or upper estuaries (Garnier et al 1995;Lemaire et al 2002;Lionard et al 2008), although this group dominates all year round. Chlorophyll b concentrations indicate the presence of chlorophytes, which were observed in abundance in upstream portions of the Rhone River by Fruget et al (1999). Chlorophytes frequently constitute the second-most important component of riverine phytoplankton after diatoms (Fruget et al 1999;Lemaire et al 2002).…”
Section: Phytoplankton Importance and Compositionmentioning
confidence: 97%
“…The present fish as semblage is a relict assemblage dominated by species with broad breeding requirements (such as roach, chub, bleak, pumpkinseed and white bream which ac counted for 88 % of the individuals) that find condi tions sufficient for them to complete their life cycle. The size class distributions of the most abundant spe cies show that recruitment occurred normally for these species during the study period (Fruget et al 1999). Most fish species forming the communities in large ri vers are long-lived species whose life-history traits (fe cundity, egg size, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the periphyton seemed more typi cal of each sampling station. Most of the taxa were ty pical of eutrophic waters in the wider sense (meso-eutrophic to eutrophic), and consisted of ubiquitous op portunistic species (Fruget et al 1999) as is often the case in nutrient-rich lowland rivers (Descy 1992, Del Giorgio et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Les aménagements hydroélectriques de Pierre-Bénite et de Péage-deRoussillon (figure 1), en aval de Lyon, sont suivis depuis plus de dix ans dans le cadre de diverses études (FRUGET, 1991 ;FRUGET et al, 1999 ;ARALEPBP, 2000). Quatre stations physiquement dissemblables, deux d'entre elles étant situées en secteurs de radiers et deux autres en secteurs lentiques endigués ( figure 1A), régulièrement échantillonnées, sont considérées dans le cadre de cette étude.…”
Section: -Site D'étude -Matériel Et Méthodesunclassified